The use of medical grade cannabis in Italy for drug-resistant epilepsy: a case series - Pane, Chiara; Saccà, Francesco (Neurological sciences, 2020)
In Italy, medical grade cannabis (MGC) can be prescribed for different medical conditions, including drug-resistant epilepsy (DRE), once standard and approved therapies have failed, or caused non-tolerable side effects. Here, we present a retrospective case series report of five patients with DRE who started therapy with MGC. Authorized ISO 9001:2008 pharmacies prepared MGC according to Italian laws. Olive oil extracts (OOEs) were prepared following standard extraction protocols, and cannabinoids were measured on each OOE to check for successful extraction.After treatment with MGC, all patients reported a reduction in seizure frequency and severity, and some reported improved mood, sleep quality, and general well-being without relevant side effects. Despite the small sample size and open-label nature of the data, we show that MGC may be successfully used to treat DRE. This is especially true when considering that no valid therapeutic option exists for these patients and that MGC was extremely well tolerated.